Penyebab Kesulitan Belajar Daring Mata Pelajaran Sosiologi Di SMA St. Fransiskus Asisi - Verontika; Warneri; Iwan Ramadhan (FKIP, Universitas Palangka Raya, 2021)
This study aims to determine the factors that cause learning difficulties of students in the online learning system on sociology subjects in class XI IPS 3 SMA St. Fransiskus Asisi Pontianak. This study uses a qualitative method with a descriptive research form. Sources of research data were students of class XI IPS 3 and teachers of sociology subjects at SMA St. Fransiskus Asisi Pontianak. The data in this study relate to learning difficulties faced by students in online learning systems in sociology subjects. The results of this study indicate the occurrence of learning difficulties of students in the online learning system caused by two factors, namely internal and external factors. The internal factor is the lack of learning motivation of students, where they feel bored and less enthusiastic in the learning process, and the lack of social interaction between students and teachers and students and students. While the external factors are due to the lack of costs and internet access on sociology subjects, during the Covid-19 pandemic it was carried out online, and students needed sufficient fees and good internet access and the factors of technical skills or poor learning habits of students caused learning difficulties in the online learning process.